2006
DOI: 10.1120/jacmp.v7i3.2212
|View full text |Cite
|
Sign up to set email alerts
|

Out‐of‐field dosimetry measurements for a helical tomotherapy system

Abstract: Helical tomotherapy is a rotational delivery technique that uses intensity‐modulated fan beams to deliver highly conformal intensity‐modulated radiation therapy (IMRT). The beam‐on time needed to deliver a given prescribed dose can be up to 15 times longer than that needed using conventional treatment delivery. As such, there is concern that this delivery technique has the potential to increase the whole body dose due to increased leakage. The purpose of this work is to directly measure out‐of‐field doses for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 28 publications
(54 reference statements)
1
31
2
Order By: Relevance
“…The TomoTherapy system has been designed with this in mind, with 23 cm of attenuation (tungsten jaws and MLC leaves), meaning that for static field delivery, leakage doses are reduced by 3 to 11 times compared to a conventional accelerator. When these factors are combined together, this results in similar, if not lower, leakage than for a conventional linac delivering IMRT (24).…”
Section: Discussionmentioning
confidence: 70%
“…The TomoTherapy system has been designed with this in mind, with 23 cm of attenuation (tungsten jaws and MLC leaves), meaning that for static field delivery, leakage doses are reduced by 3 to 11 times compared to a conventional accelerator. When these factors are combined together, this results in similar, if not lower, leakage than for a conventional linac delivering IMRT (24).…”
Section: Discussionmentioning
confidence: 70%
“…1, [8][9][10][11][12][13][14][15] Pre-estimation of peripheral dose during a given treatment is difficult because it depends on myriad factors and variables.…”
Section: -3mentioning
confidence: 99%
“…These doses are also known as "peripheral doses". In the literature, studies can be found, investigating peripheral doses on Linac and/ or Tomotherapy devices (Vanhavere et al, 2004;Balog et al, 2005;Ramsey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%